Complications of the Rigid Spine - Vanhoenacker, Filip M.; Vanhoenacker, Charlotte; Lalam, Radhesh (Seminars in Musculoskeletal Radiology, 2023)
We present a short overview of the most common causes and imaging findings of a rigid spine including long-standing spondylarthritis, diffuse idiopathic skeletal hyperostosis, and the less common ossification of the posterior longitudinal ligament. The article also focuses on the pathogenesis and imaging findings of acute complications of the rigid spine due to fractures. These fractures may occur even after minor trauma and are difficult to detect on initial radiographs, resulting in a delayed diagnosis. They are often unstable with a high risk of severe neurologic complications, leading to high morbidity and mortality both in the initial phase and in the months following the fracture. Because the negative predictive value of conventional radiography is low, every patient with a rigid spine with newly appearing pain should be referred for subsequent cross-sectional imaging.
Keywords: spine; ankylosis; complications; magnetic resonance imaging; computed tomography